The world(s) of work in transition. Conference report. ETUI-ETUC Conference, Brussels, 27-29 June 2018 - Hammerton, Sara; Poyser, David (Brussels, 2018)
"The report of the third joint ETUI-ETUC conference, held on 27-29 June 2018, summarises the three days of discussion that took place when over 500 delegates gathered in Brussels to debate the future of work. The ambition of the 2018 event was to analyse the impact of the four key ‘megatrends’ – globalization, climate change, digitalization and the demographic transition disrupting societies and economies."